(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to determine the prevalence of generalized anxiety disorder among preventive medicine students at Hanoi Medical University in the 2024-2025 academic year and to identify related factors. Materials and methods: A cross-sectional study was conducted with 411 preventive medicine students from first to sixth year at Hanoi Medical University, utilizing the Hamilton rating scale for anxiety. Results: The prevalence of generalized anxiety disorder among students was 41.6%, with mild levels accounting for 19.5%. Generalized anxiety disorder rates were significantly higher among female students (45.7%) and third-year students (51.3%). Related factors included gender (female students were 1.6 times more likely to have generalized anxiety disorder), year of study (first-to-third-year students were 2.1 times more likely than fourth-to-sixth-year students), history of anxiety disorders (risk increased by 5.0 times), dissatisfaction with exam scores (2.2 times higher risk), and academic pressure (medium pressure increased risk by 3.2 times, high pressure by 13.2 times). Family factors also played a significant role, including parental separation/divorce (2.6 times higher risk), family conflict (3.0 times higher risk), and witnessing parental arguments (2.7 times higher risk). Conclusion: The study proposes solutions to support students, such as cognitive behavioral therapy, relaxation techniques, and effective study time management. In addition, the university should consider adjusting academic workload and diversifying assessment methods.